1987
DOI: 10.1038/clpt.1987.27
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin uptake inhibitor citalopram attenuates ethanol intake

Abstract: No effective drug for decreasing ethanol intake is available for clinical use. Our previous studies showed that zimeldine decreased ethanol intake in rats and nondepressed alcohol abusers. However, zimeldine was withdrawn from the market because of serious toxicity. We tested citalopram, a selective serotonin uptake inhibitor, in 39 male nondepressed early-stage problem drinkers (aged 19 to 61 years). Subjects were randomly allocated to receive either citalopram, 20 (n = 20) or 40 (n = 19) mg/day orally, or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(50 citation statements)
references
References 0 publications
0
49
0
1
Order By: Relevance
“…The selective serotonin reuptake inhibitors (SSRIs) zimelidine, citalopram, viqualine, and fluoxetine were shown to produce modest decreases in alcohol consumption in nondepressed heavy drinkers (Naranjo et al 1984(Naranjo et al , 1987(Naranjo et al , 1989(Naranjo et al , 1990. However, when fluvoxamine was combined with cognitive-behavioral therapy to treat alcohol dependence, the medication was poorly tolerated and seemed to be unsuitable for use among patients with this disorder (Kranzler et al 1993).…”
mentioning
confidence: 99%
“…The selective serotonin reuptake inhibitors (SSRIs) zimelidine, citalopram, viqualine, and fluoxetine were shown to produce modest decreases in alcohol consumption in nondepressed heavy drinkers (Naranjo et al 1984(Naranjo et al , 1987(Naranjo et al , 1989(Naranjo et al , 1990. However, when fluvoxamine was combined with cognitive-behavioral therapy to treat alcohol dependence, the medication was poorly tolerated and seemed to be unsuitable for use among patients with this disorder (Kranzler et al 1993).…”
mentioning
confidence: 99%
“…Alcoholics exhibit abnormalities in a host of parameters of 5-HT function: decreased plasma levels of tryptophan (Branchey et al 1981); a decreased plasma ratio of tryptophan to other amino acids that compete with it for transport (Branchey et al 1981); decreased platelet 5-HT content (Bailly et al 1993); and increased platelet 5-HT uptake (Daoust et al 1991). Abstinent alcoholics have also been found to exhibit lower cerebrospinal fluid (CSF) levels of the major 5-HT metabolite, 5-hydroxyindole acetic acid (5-HIAA; Ballenger et al 1979), which normalized after 1 week of drinking (Zarcone et al 1975 (Naranjo et al 1984(Naranjo et al , 1987. In aggregate, the evidence indicates that dysfunction in 5-HT neurotransmission may be associated with a propensity toward alcohol abuse and dependence.…”
Section: Data In Animals and Adults Indicate That Central Serotonergimentioning
confidence: 99%
“…Furthermore, several studies have found blunted prolactin (PRL) and ր or cortisol (CORT) responses to challenge with 5-HT agents such as fenfluramine (FEN;Balldin et al 1994), m-clorophenylpiperazine (m-CPP; Krystal et al 1996), and 6-chloro-2-1-piperazinylpyrazine (MK-212; in alcoholics, suggesting deficits in central 5-HT function. Finally, clinical trials have found that the 5-HT uptake inhibitors zimeldine and citalprom decreased alcohol intake (Naranjo et al 1984(Naranjo et al , 1987.…”
mentioning
confidence: 99%
“…Both short-term 80 and long-term 81 administration of zimelidine, a selective serotonin-reuptake inhibitor (SSRI) that was removed from clinical trials because of toxicity, have shown that it attenuates ethanol consumption. Other SSRIs that have been tested in humans to reduce alcohol consumption include citalopram, 82,83 viqualine, 84 fluoxetine, [85][86][87][88][89] and fluvoxamine. 90 The results from these studies have been mixed.…”
Section: Treatment Of Alcohol Dependencementioning
confidence: 99%
“…90 The results from these studies have been mixed. Whereas some studies have shown modest effects, [80][81][82][83][84][85]87 others have shown these medications to be poorly tolerated 90 or inefficacious. 88,89 Gerra et al 86 found that fluoxetine was superior to placebo in reducing the number of drinks consumed daily only among subjects with a positive parental history of problem drinking.…”
Section: Treatment Of Alcohol Dependencementioning
confidence: 99%